Transient Global Amnesia with Reversible White Matter Lesions: A Variant of Posterior Reversible Encephalopathy Syndrome? - Tomoki Nakamizo; Ippei Tsuzuki; Takashi Koide (Case Reports in Neurological Medicine)
Transient global amnesia (TGA) is a self-limited disease characterized by isolated amnesia, which resolves within 24 h. In contrast, posterior reversible encephalopathy syndrome (PRES) is a potentially life-threatening disease that usually presents with seizures, altered mental status, headache, and visual disturbances. It is characterized by reversible vasogenic edema that predominantly involves the parieto-occipital subcortical white matter as shown by neuroimaging studies. To date, there have been no reported cases of PRES with a clinical course resembling TGA. Here we report the case of a 58-year-old woman who presented with isolated amnesia and headache. On admission, her blood pressure was 187/100 mmHg. She had complete anterograde amnesia and slight retrograde amnesia without other neurological findings. After the treatment of her hypertension, the amnesia resolved within 24 h. Although the initial magnetic resonance image (MRI) was almost normal, the fluid attenuation inversion recovery (FLAIR) images of the MRI on the next day revealed several small foci of high intensity areas in the fronto-parieto-occipital subcortical white matter, presumed to be vasogenic edema in PRES. The lesions disappeared one month later. This case suggests that PRES can mimic the clinical course of TGA. PRES should be considered in the differential diagnosis for TGA.